Comparison of glucose derivatives effects on cartilage degradation - Thanyaluck Phitak (2018)
Background. Glucosamine (GlcN) is a well-recognized candidate for treatment of osteoarthritis. However, it is currently used in derivative forms, such as glucosamine-hydrochloride (GlcN-HCl) or glucosamine sulfate (GlcN-S). However, the molecular mode of action remains unclear. In this study, we compared the effects of Glucose (Glc), Glucuronic acid (GlcA), Glucosamine hydrochloride (GlcN-HCl) and Glucosamine sulfate (GlcN-S) on cartilage degradation. Methods. Porcine cartilage explants were co-cultured with recombinant human IL-1β and each tested substance for 3 days. HA, s-GAG and MMP-2 releases to media were measured using ELISA, dye-binding assay and gelatin zymography, respectively. Similar studies were performed in a human articular chondrocytes (HAC) monolayer culture, where cells were co-treated with IL-1β and each reagent for 24 hours. Subsequently, cells were harvested and gene expression measured using RT-PCR. All experiments were carried out in triplicate. Student's t-tests were used for statistical analysis. Results. In cartilage explants treated with IL-1β, GlcN-S had the highest chondroprotective activity of all four chemicals as shown by the inhibition of HA, s-GAG and MMP-2 released from cartilage. The anabolic (aggrecan core protein; AGG, SOX9) and catabolic (MMP-3, -13) genes in HACs treated with IL-1β and with/without chemicals were studied using RT-PCR. It was found that, GlcN-HCl and GlcN-S could reduce the expression of both MMP-3 and -13 genes. The IL-1β induced-MMP-13 gene expression was decreased maximally by GlcN-S, while the reduction of induced-MMP-3 gene expression was greatest with GlcN-HCl. Glc and GlcA reversed the effect of IL-1β on the expression of AGG and SOX9, but other substances had no effect. Conclusion. This study shows that glucosamine derivatives can alter anabolic and catabolic processes in HACs induced by IL-1β. GlcN-S and GluN-HCl decreased induced MMP-3 and -13 expressions, while Glc and GlcA increased reduced-AGG and SOX9 expression. The chondroprotective study using porcine cartilage explant showed that GlcN-S had the strongest effect. © 2010 Phitak et al; licensee BioMed Central Ltd.